Force Majeure Clause in Umrah Contract: Safeguarding Malaysian Umrah Travellers Post-COVID-19 Pandemic - Wan Noor Fatihah Wan Kamarudin; Ghapa, Norhasliza; Noraida Harun; Farhanin Abdullah Asuhaimi; Iyllyana Che Rosli (Yuridika, 2025)
Thousands of Umrah trips were cancelled by the domestic tour operators after the Saudi government restricted travel to the Holy City of Mecca and Medina due to the rapid spread of COVID-19 in March 2020. As a result, how domestic tour operators handle this unique situation varies. Certain tour operators offering Umrah services depended on the force majeure clause in their contract, which released them from fulfilling their obligations under the agreement. However, a small number of businesses did not include force majeure clauses in their Umrah contracts, which allow the Umrah tour operators to excuse themselves from fulfilling their obligations even terminating the Umrah contract without providing the pilgrims with any compensation. Due to unstandardised Umrah contracts prepared by the domestic tour operators, it detrimentally affects the interests of vulnerable pilgrims. Considering this, this study aims to provide a mechanism in safeguarding the interests of Umrah travellers in the event of unforeseen occurrences. As such, the doctrinal study that forms the basis of this article uses a qualitative methodology, with data gathered via library research. The study concludes that in situations where a force majeure incident interferes with the performance of the Umrah contract, the Umrah tour operators have not adhered to any standard procedure. It is urgent for the domestic Umrah tour operators to invoke force majeure clauses in their Umrah contracts.